Necessary endings : the employees, businesses, and relationships that all of us have to give up in order to move forward - Cloud, Henry (HarperBusiness, 2010)
Knowing when and how to let go when something, or someone isn't working is essential for happiness and success. Cloud gives readers the tools they need to say good-bye and move on.